Relationship Between Gender Reveal Parties and Popular Pregnancy Rituals Held by Pregnant Women, and Their Self-Perception and Effects of Social Media: A Cross-Sectional Study - Aysun Ekşioğlu; Sude Kırmızıoğlu (Journal of Transcultural Nursing, 2026)
Introduction: Pregnancy rituals such as gender-reveal parties and baby showers have become increasingly visible through social media and may influence pregnant women’s perceptions of motherhood and body image. This study examined the relationship between participation in pregnancy rituals, pregnant women’s self-perception, and social media influence. Methods: A cross-sectional survey was conducted with 287 pregnant women attending prenatal care at a tertiary hospital in western Türkiye. Results: Overall, 42.5% of participants performed at least one pregnancy ritual, and 40.8% held a gender-reveal party. Women participating in rituals had higher motherhood perception scores and greater social media influence. Social media influence was the strongest predictor of ritual participation ( p < .001). Discussion: Pregnancy rituals appear to be shaped by digital culture and are associated with pregnant women’s psychosocial self-perceptions. Prenatal counseling should address the influence of social media on maternal well-being.